The influence of body development of adult female Boophilus microplus ticks on their eggs fertility - Sutiastuti Wahyuwardani (Jurnal Ilmu Ternak dan Veteriner, 1995)
One hundred and seventy six adult female cattle ticks, Boophilus microplus, were collected to observed the influence of their body development on their eggs fertility under laboratory conditions (22°-32°C and 84-92% relative humidity) . The regression analysis result shown that as the body developed, eggs production and eggs fertility increased, but there was no correlation between ticks weight and the incubation periode . The relation between ticks weight and eggs production was shown as Y = -309 .433 + 13 .868X and r = 98 .5 % whereas the influence of ticks body development on eggs fertility was shown as Y = 8 .224 + 0 .338X, r = 92 .0% and the incubation periode was about 21-26 days . The fertile eggs begin to be produced by ticks with body weight of about 35-49 mg and fertility 28.39%.